Novel Possibilities : Fiction and the Formation of Early Victorian Culture - Childers, Joseph W. (Book collections on Project MUSE., 1995)
Childers contends that novels such as Benjamin Disraeli's Coningsby, Elizabeth Gaskell's Mary Barton, and Charles Kingsley's Alton Locke were in direct competition with other forms of public discourse for interpretive dominance of their age. Childers examines the interactions between the novel and a set of texts generated by parliamentary and radical politics, the sanitation reform movement, and religion. Reversing the position of earlier studies of this period, he argues that the novel was in fact constitutive of - and often provided the model fortexts as diverse as the political agendas of Robert Peel and T.B. Macaulay or Edwin Chadwick's enormously important Report on the Sanitary Condition of the Labouring Population of Great Britain, with its seemingly encyclopedic description of the conditions of poverty.